Patterns of lateral enamel growth in Homo naledi as assessed through perikymata distribution and number. Issue 121 (August 2018) - Guatelli-Steinberg, Debbie; O'Hara, Mackie C.; Le Cabec, Adeline; Delezene, Lucas K.; Reid, Donald J.; Skinner, Matthew M.; Berger, Lee R.
Abstract: Perikymata, incremental growth lines visible on tooth enamel surfaces, differ in their distribution and number among hominin species, although with overlapping patterns. This study asks: (1) How does the distribution of perikymata along the lateral enamel surface of Homo naledi anterior teeth compare to that of other hominins? (2) When both perikymata distribution and number are analyzed together, how distinct is H. naledi from other hominins? A total of 19 permanent anterior teeth (incisors and canines) of H. naledi were compared, by tooth type, to permanent anterior teeth of other hominins: Australopithecus afarensis, Australopithecus africanus, Paranthropus robustus, Paranthropus boisei, Homo ergaster / Homo erectus, other early Homo, Neandertals, and modern humans, with varying sample sizes. Repeated measures analyses of the percentage of perikymata per decile of reconstructed crown height yielded several statistically significant differences between H. naledi and other hominins. Canonical variates analysis of percentage of perikymata in the cervical half of the crown together with perikymata number revealed that, in 8 of 19 cases, H. naledi teeth were significantly unlikely to be classified as other hominins, while exhibiting least difference from modern humans (especially southern Africans). In a cross-validated analysis, 68% of the H. naledi teeth were classified as such, while 32% were classified as modern human (most often southern African). Of 313 comparative teeth use for this analysis, only 1.9% were classified as H. naledi . What tends to differentiate H. naledi anterior tooth crowns from those of most other hominins, including some modern humans, is strongly skewed perikymata distributions combined with perikymata numbers that fall in the middle to lower ranges of hominin values. H. naledi therefore tends toward a particular combination of these features that is less often seen in other hominins. Implications of these data for the growth and development of H. naledi anterior teeth are considered.